Therapeutic Applications of Dental Mesenchymal Stem Cells in Alzheimer’s Disease—A Scoping Review - Rupali Agnihotri; Sumit Gaur (Dentistry Journal)
Background/Objectives: Alzheimer’s disease (AD), a neurodegenerative condition, produces dementia and cognitive debility. Lately, preclinical models of AD have shown neuroregenerative potential of mesenchymal stem cells of dental origin (DMSC). This scoping review aims to map and synthesize the evidence on the therapeutic applications of DMSCs in AD management. Methods: This review followed the Arksey and O’Malley framework for scoping reviews and PRISMA-ScR guidelines. Scopus, Medline (Pubmed), Web of Science, and Embase databases were searched for published literature until February 2025. Data was mapped according to the type of DMSC and their therapeutic properties useful in AD management, like neuro differentiation, neuroprotection through increased neuron number and vitality, anti-neuroinflammation, mitochondrial repair, and improved cognition. Results: A total of 22 articles were included. A research gap existed, as most studies were preclinical (in vitro and animal models) with no clinical trials in humans. Furthermore, they mostly evaluated neuroregenerative properties of dental pulp stem cells (DPSC) and stem cells from human-exfoliated deciduous teeth (SHED), while Periodontal ligament stem cells (PDLSC) were least studied. All the DMSCs were neuroprotective and increased neuron number and vitality. Neurodifferentiation was reported in DPSCs and PDLSCs, while DPSCs and SHEDs showed anti-neuroinflammation, mitochondrial repair, and improved cognition in AD animal models. Conclusions: Although the DPSCs and SHEDs showed promising outcomes in preclinical models of AD, a gap exists as results have not been translated into human clinical trials. Future advances may identify plausible ways of applying the DMSCs to regain the lost neurons and re-establish a healthy brain microenvironment.